2018
DOI: 10.3390/met8110970
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Weak Zones in Friction Stir Welded Magnesium Alloys from the Viewpoint of Local Texture: A Short Review

Abstract: Friction stir welding (FSW) is a promising approach for the joining of magnesium alloys. Although many Mg alloys have been successfully joined by FSW, it is far from industrial applications due to the texture variation and low mechanical properties. This short review deals with the fundamental understanding of weak zones from the viewpoint of texture analysis in FSW Mg alloys, especially for butt welding. Firstly, a brief review of the microstructure and mechanical properties of FSW Mg alloys is presented. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 101 publications
(126 reference statements)
1
8
0
Order By: Relevance
“…The mechanical properties of FSW joint are lower than that of base material. The decreasing of mechanical properties can be described to the texture of SZ side, favorable for extension twinning and basal slip [ 3 , 15 ]. Based on the mechanical properties, the tensile tests were terminated when the stress level was up to 90% of UTS, and then the specimens were prepared for the microstructure examination.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanical properties of FSW joint are lower than that of base material. The decreasing of mechanical properties can be described to the texture of SZ side, favorable for extension twinning and basal slip [ 3 , 15 ]. Based on the mechanical properties, the tensile tests were terminated when the stress level was up to 90% of UTS, and then the specimens were prepared for the microstructure examination.…”
Section: Resultsmentioning
confidence: 99%
“…However, the hexagonal close packed structure is a negative factor for the formability of Mg alloys [ 2 ]. As a solid-state joining technology, the friction stir welding (FSW) is useful for improving the joining of Mg alloys [ 3 , 4 ]. FSW has been successfully applicated in several Mg alloys systems, such as AZ (Mg–Al–Zn) and AM (Mg–Al–Mn) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] As a solid‐state welding technology, friction stir welding (FSW) has a significant advantage in the joining of Mg alloys. [ 2 ] Severe plastic deformation and full recrystallization occur in the FSW process, [ 3–5 ] which causes significant grain refinement, and forms a strong local texture in the weld zone (WZ) of Mg alloys. [ 4,6–8 ] Then, some regions with a soft‐oriented texture are formed in the WZ and significantly reduced the tensile properties, especially for the yield strength (YS).…”
Section: Introductionmentioning
confidence: 99%
“…Twin-orientation depends on twin variant selection during deformation [18]. Previous reports indicated that continuous bending, in-plane shear and in-plane compression favorably activate one twin variant in each grain and generate single twin-texture [11][12][13][14][15]19]. It has been reported that change of strain path can promote the activation of multiple twin variations to further randomize twin-texture [20].…”
Section: Introductionmentioning
confidence: 99%